Answer:
[tex]w = -6[/tex]
Step-by-step explanation:
Solve for [tex]w[/tex]:
[tex]2(w - 9) = 5w + 6 + w[/tex]
-Use Distributive Property:
[tex]2(w - 9) = 5w + 6 + w[/tex]
[tex]2w - 18 = 5w + 6 + w[/tex]
-Combine like terms:
[tex]2w - 18 = 5w + 6 + w[/tex]
[tex]2w - 18 = 6w + 6[/tex]
-Subtract [tex]6w[/tex] from [tex]2w[/tex] :
[tex]2w - 6w - 18 = 6w - 6w + 6[/tex]
[tex]-4w - 18 = 6[/tex]
-Add [tex]18[/tex] on both sides :
[tex]-4w - 18 + 18 = 6 + 18[/tex]
[tex]-4w = 24[/tex]
-Take [tex]4w[/tex] divide it on both sides of the equation:
[tex]\frac{-4w}{-4} = \frac{24}{-4}[/tex]
[tex]w = -6[/tex]
Therefore, the value of [tex]w[/tex] is [tex]-6[/tex].